THE EFFECT OF DEMONSTRATIVE AND INTERACTIVE LEARNING VIDEOS ON INSTAGRAM SOCIAL MEDIA ON DIGITAL LITERACY - Mentari Anugrah Imsa; Farah Zyiafira; Khairum Tri Anissa; Reja Ruhul Fasya; Sandrina Irsa Adelia (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Technological advancements have had a broad impact, including in the field of education, where social media is increasingly used to implement microlearning. However, this progress also demands digital literacy skills from its users. This study was conducted to examine the effect of digital literacy videos uploaded on social media as a learning medium. The research aims to determine whether there is a difference in the level of digital literacy among students after being exposed to demonstrative and interactive videos uploaded on social media. The videos were designed based on microlearning principles, breaking down the learning material into smaller segments to enhance learner retention. This research employed a quantitative experimental design, with active university students in Jakarta as respondents. The results indicate that interactive videos significantly impact digital literacy levels, whereas demonstrative videos do not. Therefore, this study recommends educational institutions begin offering microlearning materials, especially through audiovisual media or videos